Analysis of Use Cases and Use Case Estimation (International Journal of Engineering and Computer Science, 2017)
Use case analysis is a major technique used to find out the functional requirements of a software system. Use case, an important concept in use case analysis, represents an objective user wants to achieve with a system. It can be in text form, or be visualized in a use case diagram. There are different approaches and methods to successfully estimate effort using use cases. This Paper describes use cases and how to write them, and presents the Use Case Points method. It also describes related work on estimating with use cases. Keywords: Use case, Use case point methods, software project estimation.